A study on multiple melting of isotactic polypropylene - Kim, YC; Ahn, W; Kim, CY (SOC PLASTICS ENG INC, 1997)
Multiple melting characteristics of a highly isotactic polypropylene (iPP) were studied by means of differential scanning calorimetry (DSC). Double melting characteristics were observed on melting IPP crystallized isothermally at temperatures ranging from 110 to 140 degrees C. iPP crystallized below and above 125 degrees C exhibited different double melting characteristics from each other. For iPP crystallized below 125 degrees C, the single melting peak split into two peaks during slow DSC heating scans without changing the total crystallinity in the polymer. On the other hand, the double melting endotherm of iPP crystallized above 125 degrees C seemed to come from two preexisting crystal fractions having different T-m. There existed an optimum annealing temperature range where the five-minute annealing of iPP raised T-m of the polymer significantly. The treatment also increased the crystallinity of iPP crystallized isothermally at 110 degrees C by 12%.
Keywords: BEHAVIOR